2017
DOI: 10.1149/2.0121714jes
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids Electrodeposition of Sn with Different Structures as Anodes for Lithium-Ion Batteries

Abstract: Electrodeposition of tin (Sn) on a Ni electrode has been investigated in three ionic liquids, i.e., 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIm]BF 4 ), 1-ethyl-3-methylimidazolium trifluoromethylsulfonate ([EMIm]TfO) and 1-ethyl-3-methylimidazolium dicyanamide ([EMIm]DCA). Sn(II) ion was introduced into the ionic liquids by dissolving SnCl 2 . The different redox potentials of the Sn(II)/Sn couple imply that different Sn(II) species were formed in these solvents. Voltammetric studies reveal that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…The non-zero intercept may be assigned to an adsorption phenomena and some surface chemical coupled reactions. 29,43 The diffusion coefficient of Sn 2+ species, 27,29,30 probably due to higher viscosity for [EMIm + ][TFSI -] that induced a lower mobility of Sn 2+ . Moreover, because the coordination state of Sn 2+ is modified by the counter ion solvation force of the ionic liquid anion versus the counter-ion of Sn precursor, different solvation environments influencing Sn 2+ mobility are expected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-zero intercept may be assigned to an adsorption phenomena and some surface chemical coupled reactions. 29,43 The diffusion coefficient of Sn 2+ species, 27,29,30 probably due to higher viscosity for [EMIm + ][TFSI -] that induced a lower mobility of Sn 2+ . Moreover, because the coordination state of Sn 2+ is modified by the counter ion solvation force of the ionic liquid anion versus the counter-ion of Sn precursor, different solvation environments influencing Sn 2+ mobility are expected.…”
Section: Resultsmentioning
confidence: 99%
“…The multi-step lithiation delithiation processes on Sn electrode 3,29,44 as on Sn based alloy electrode 29,[45][46][47][48] are already well documented, and it has already been concluded that CV profiles and peak potentials are in both cases characteristic of electrodes containing metallic tin. Especially the plateau of potential attributed to the lithiation of Cu6Sn5 arise in the same domain of potential where intermetallic tin-lithium phases prevails.…”
Section: Electrochemical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The electrochemical deposition of tin and its alloys is of great practical importance and widely used in the semiconductor industry and field of energy storage devices [1][2][3][4], like lithium ion batteries; e.g., traditional electrodeposition of tin and its alloy is performed in aqueous electrolytes including sulfate, fluoborate, and citrate [5][6][7]. Such electrolytes are susceptible to complex electrolyte composition and quite corrosive and can possibly have a negative impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition of tin has been investigated in some ionic liquids [4,14], especially AlCl 3 -based ionic liquids [15]. However, this kind of ionic liquid is sensitive to air and water; therefore the experiment must be carried out under inert gas conditions.…”
Section: Introductionmentioning
confidence: 99%